Prezentacja frazeologiczna pola konceptualnego „Память’” / „Pamięć” w języku rosyjskim i polskim - Sitarski, Andrzej (Studia Rossica Posnaniensia, 2020)
In the article the author analyses Russian and Polish phrasemes that represent the conceptual field ”Memory” in both linguacultural spaces. In order to do this he relies on the postulates of Ryszard Tokarski’s theory of semantic connotation being the theory of the secondary semantic field, which constitutes the optional layer of the lexical meaning of a linguistic sign. On the basis of the conducted analysis of the selected phraseological data it can be concluded that the Polish and Russian commonsense attitude to the semantic interpretation of memory is similar. Additional connotative senses can be determined in this case, which are of an evaluative, emotional and stylistic nature.